The relationship between intergenerational cash transfers, financial status and labour force participation of older men and older women in Malaysia - Chang, Foo Chung (2023)
An ageing society is a global phenomenon, and it has a great impact on all facets of human life. It is one of the most challenging issues to any country regardless of its status. Ageing population is growing at an alarming rate in Malaysia and Malaysia is already an ageing country as the population of older persons accounted for 7.4 percent, and it is expected to double by 2030. One of Malaysia’s aspirations is to create an active and healthy ageing society but it is yet to be realised. Current studies on the labour force participation of older people in Malaysia are still limited and a range of questions on aspects of family life, financial security and well-being of the older people especially staying in the rural areas in Malaysia, are still yet to be explored. Many studies focused on the labour force participation of older people in general rather than segregating it between older men and older women. There is a limited study specifically on labour force participation of older men and older women in Malaysia and hence, this study will extend the existing studies by distinguishing the older people by their gender and exploring more variables that are commonly associated with the labour force participation decision of older people such as demographic, socio-economic, health, geographical, intergenerational cash support and financial variables using most optimal data collected via the Malaysian Population and Family Survey (MPFS) conducted by the National Population and Family Development Board (NPFDB) under the Ministry of Women, Family and Community Development in Malaysia. The survey was conducted on 4,059 respondents aged 60 and above. This study employed logistic regression analysis in investigating the relationship of the selected explanatory variables with the labour force participation decision of older men and older women in Malaysia. Based on the logistic regression analysis, labour force participation of older women has a significant relationship with marital status, ethnicity, number of living children and religion, but the labour force participation of older men shows insignificant relationship to these factors. Factors like health status, region and savings are significantly related with the labour force participation of older men but show insignificant relationship with the labour force participation of older women. Some financial variables such as income level and investment status were found to have no significant relationship with the labour force participation decision by both older men and older women in Malaysia. The study discovered that the magnitude change in the associations of the labour force participation between older men and older women with age, and number of difficulties in Activities of Daily Living (ADLs) are varied. The magnitude change in odds of working for older men is greater than older women when their age and number of difficulties in ADLs increase. The findings from the study enable the policymakers to design a better ageing policy by incorporating more effective incentive and recruitment systems for the older people with minimal to no effects on the employment opportunities for the young adults. The intergenerational cash support can be explored further in terms of its direction and the cash transfers by working adult grandchildren to their older grandparents. These were not covered in the MPFS-54 survey which could shed more information on how an older person made his or her decision whether to join the labour force or not. This study also provides more opportunities for future research to enrich the findings of this study from different aspects of the labour force participation of older people in Malaysia.